Hypovirus infection induces proliferation and perturbs functions of mitochondria in the chestnut blight fungus - Wang, Jinzi; Quan, Rui; He, Xipu; Fu, Qiang; Tian, Shigen; Zhao, Lijiu; Li, Shuangcai; Shi, Liming; Li, Ru; Chen, Baoshan (Frontiers in Microbiology, 2023)
The chestnut blight fungus, Cryphonectria parasitica, and hypovirus have been used as a model to probe the mechanism of virulence and regulation of traits important to the host fungus. Previous studies have indicated that mitochondria could be the primary target of the hypovirus. Here we report a comprehensive and comparative study comprising mitochondrion quantification, reactive oxygen species (ROS) and respiratory efficiency, and quantitative mitochondrial proteomics of the wild-type and virus-infected strains of the chestnut blight fungus. Our data show that hypovirus infection increases the total number of mitochondria, lowers the general ROS level, but increases the mitochondrial respiratory efficiency. Quantification of mitochondrial proteomes revealed that a set of proteins functioning in energy metabolism and mitochondrial morphogenesis as well as virulence were regulated by the virus. In addition, two viral proteins, p29 and p48, were found to co-fractionate with the mitochondrial membrane and matrix. These results suggest that hypovirus perturbs the host mitochondrial functions to result in hypovirulence.